The Factors Affecting Performance of Employee at the Semidang Alas Maras Sub-District Office Seluma Regency - Sekuan Efendi; Ida Angriani; Abdul Rahman (Penerbit Jurnal Indonesia, 2021)
This research is an article that raises the performance of employees. In this study, it focuses more on what factors affect employee performance at the Semidang Alas Maras Sub-district Office, Seluma Regency, especially for individual factors, psychological factors and organizational factors. The research method uses quantitative methods and data analysis with multiple linear regression test with SPSS for windows version 23 application. The results of data processing prove that there is a significant influence for individual factors, psychological factors and organizational factors on the performance of the employees of the Semidang Alas Maras Subdistrict Office, Seluma Regency. The effect on the performance of the employees of the Semidang Alas Maras Sub-district Office, Seluma Regency, is seen from the beta coefficient value, namely the psychological factor has a standard beta coefficient value of 0.201, then followed by organizational factors which have a standard coefficient value of beta 0.129 while for individual factors has a standard coefficient value of beta 0.074 . From the analysis of the data produced, it can be concluded that psychological factors are the dominant factors that have the greatest influence on the tendency of employee performance at the Semidang Alas Maras Subdistrict Office, Seluma Regency.